Modelling Elastic Behaviour of Soft Tissues. Part I. Isotropy - Jemioło, S.; Telega, J.J. (Engineering Transactions, 2001)
Soft tissues mostly exhibit strongly nonlinear behaviour while undergoing large strains. New macroscopic models for both isotropic and transversely isotropic soft tissues have been proposed. The models developed are suitable for finite element formulation. It the first part of the paper isotropic models have been proposed. Implementation in the FEM programme ABAQUS has been discussed. Muscle contraction models have also been concisely reviewed.